An experiential approach to teaching qualitative research - Evans, Ken (European Journal for Qualitative Research in Psychotherapy, 2006)
The research is a phenomenological exploration of the experience of teaching research experientially, via an exploration of the experience of shame among Gestalt therapists in Norway, Sicily, United Kingdom and the Czech Republic between 2002 and 2005.